Multi-Instantons in Higher Dimensions and Superstring Solitons - Loginov, E.K (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
We construct octonionic multi-instantons for the eight- and seven-dimensional Yang-Mills theories. Extended soliton solutions to the low-energy heterotic field theory equations of motion are constructed from these octonionic multi-instantons. The solitons describe a string in ten-dimensional Minkowski space, and preserve one and two of the sixteen space-time supersymmetries correspondingly.